Association of pre and intraoperative variables with postoperative complications in coronary artery bypass graft surgery - Gimenes, Camila; Barrile, Silvia Regina; Martinelli, Bruno; Ronchi, Carlos Fernando; Arca, Eduardo Aguilar; Gimenes, Rodrigo [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2013)
Objective: To associate the pre- and intraoperative variables with postoperative complications of patients undergoing coronary artery bypass graft surgery. Methods: The pre- and intraoperative risk factors of individuals of both genders with diagnosis of coronary insufficiency undergoing coronary artery bypass graft have been studied. Results: Fifty-eight individuals with median age 62 ± 10 yearold were included in the study, 67% of whom were male. Fourteen (24.1%) patients were smokers, 39 (67.2%) had previous myocardial infarction history, 11 (19%) had undergone coronary angioplasty, 74% had hypertension, 27% had diabetes mellitus, 64% had dyslipidemia and 15.5% had chronic obstructive pulmonary disease. Eighteen (31%) patients presented postoperative complications, most frequent being: infection in surgical incision, difficulties in deambulation, dyspnea, urinary infection and generalized weakness. Male patients had fewer complications than females (P=0.005). Patients with chronic obstructive pulmonary disease remained hospitalized for longer time periods (P=0.019). Postoperative complications occurred in 50% of the patients with creatinine increased, while only 27.1% of the patients with normal value of creatinine had complications (P=0.049). In addition, complications occurred in 50% of the patients with diabetes mellitus, while only 23.8% of patients without diabetes mellitus had complications (P=0.032). The intraoperative factors showed no statistically significant differences. Conclusion: The preoperative factors are associated with postoperative complications in patients undergoing coronary artery bypass graft surgery.

Objetivo: Associar variáveis pré e intraoperatórias com as complicações pós-operatórias de pacientes submetidos à cirurgia de revascularização miocárdica. Métodos: Foram estudados os fatores de risco pré e intraoperatórios de indivíduos de ambos os sexos, com diagnóstico de insuficiência coronariana, submetidos à cirurgia de revascularização do miocárdio. Resultados: Participaram do estudo 58 indivíduos, com idade média de 62 ± 10 anos e 67% eram do sexo masculino. Catorze (24,1%) pacientes eram fumantes, 39 (67,2%) apresentavam história de infarto do miocárdio prévia, 11 (19%) tinham realizado angioplastia coronariana, 74% apresentavam hipertensão arterial, 27% diabetes mellitus, 64% dislipidemia e 15,5% doença pulmonar obstrutiva crônica. Dezoito (31%) pacientes apresentaram complicações no pós-operatório e as mais frequentes foram infecção na incisão cirúrgica, dificuldades na deambulação, dispneia, infecção urinária e fraqueza generalizada. Pacientes do sexo masculino apresentaram menos complicações que os do sexo feminino (P=0,005). Pacientes com diagnóstico de doença pulmonar obstrutiva crônica permaneceram maior tempo hospitalizados (P=0,019). Complicações pós-operatórias ocorreram em 50% dos pacientes com creatinina aumentada, enquanto que apenas 27,1% dos pacientes com valor normal de creatinina apresentaram complicações (P=0,049). Ocorreram também complicações em 50% dos pacientes com diabetes mellitus, enquanto que apenas 23,8% dos pacientes sem diabetes mellitus tiveram complicações (P=0,032). Os fatores intraoperatórios não apresentaram diferenças significativas estatisticamente. Conclusão: Os fatores pré-operatórios estão associados com complicações pós-operatórias em pacientes submetidos à cirurgia de revascularização miocárdica.
Associação de variáveis pré e intraoperatórias com complicações pós-operatórias em cirurgia de revascularização do miocárdio
Keywords: Myocardial revascularization; Coronary artery bypass; Postoperative complications; Risk factors; Revascularização miocárdica; Ponte de artéria coronária; Complicações pós-operatórias; Fatores de risco